2016
DOI: 10.1186/s12889-016-3480-4
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in underlying beliefs of socio-cognitive factors related to diet and physical activity in lower-educated Dutch, Turkish, and Moroccan adults in the Netherlands: a focus group study

Abstract: BackgroundUnhealthy eating patterns and a lack of physical activity (PA) are highly prevalent in most Western countries, especially among lower-educated people, including people of non-Western origin. The aim of this study was to investigate and compare the beliefs and barriers that underlie socio-cognitive and planning constructs related to healthy eating and PA among lower-educated Dutch, Turkish, and Moroccan adults.MethodsFocus group interviews were conducted with 90 Dutch, Turkish, and Moroccan lower-educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 60 publications
10
25
1
Order By: Relevance
“…The results showed that how people perceived a healthy diet was mostly represented at the level of food product (vegetables and fruit) and the content/nutrient level (carbohydrates); whereas how they would like to eat healthily was mostly represented at the level of food processing (processing), food product (vegetables) and dietary patterns (amount) [7,19]. This is in line with previous studies in which many participants named fruit and vegetables as part of a healthy diet [11][12][13]. A striking finding was that only five participants explicitly called the Wheel of Five as how they would describe a healthy diet.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results showed that how people perceived a healthy diet was mostly represented at the level of food product (vegetables and fruit) and the content/nutrient level (carbohydrates); whereas how they would like to eat healthily was mostly represented at the level of food processing (processing), food product (vegetables) and dietary patterns (amount) [7,19]. This is in line with previous studies in which many participants named fruit and vegetables as part of a healthy diet [11][12][13]. A striking finding was that only five participants explicitly called the Wheel of Five as how they would describe a healthy diet.…”
Section: Discussionsupporting
confidence: 81%
“…Another study found that more fish and more lean meat were also part of the healthy eating definition in a large Spanish sample [12]. A more recent study found that low-educated Dutch, Turkish, and Moroccan adults living in the Netherlands considered mainly fruit and vegetables as part of a healthy diet [13]. Thus, fruit, vegetables, (avoiding or limiting) meat, balance/variety/moderation, and less fat seem to constitute a healthy diet according to many consumers; these elements were also identified by a review [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in the present study, the samples originated from 31 different countries. It is likely that cultural context influences the moderating effect of SES on the relationships between TPB variables and diet, as cross‐cultural research shows that different countries have different attitudes towards food (Rodriguez‐Arauz, Ramirez‐Esparza, & Smith‐Castro, ) and different cultural norms regarding eating behaviours (Romeike, Abidi, Lechner, de Vries, & Oenema, ). Furthermore, how dietary behaviour was measured (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of social support from relatives was another constraint (Koca et al, ). Religious customs and the absence of recreational facilities where men and women can exercise separately can be additional barriers (Ozturk & Koca, ; Romeike, Abidi, Lechner, de Vries, & Oenema, ). Notably, <10 participants in this study had a Spirituality, Caretaking/parenting, or Interpersonal relationship problem.…”
Section: Discussionmentioning
confidence: 99%